The different outcomes in the elderly with subclinical hypothyroidism diagnosed by age-specific and non-age-specific TSH reference intervals: a prospectively observational study protocol - Zhang, Xueqi; Li, Yang; Jin, Jing; Wang, Huangman; Zhao, Bozun; Wang, Songwen; Shan, Zhongyan; Teng, Weiping; Teng, Xiaochun (Frontiers in Endocrinology, 2023)
Introduction Subclinical hypothyroidism (SCH) is a common endocrine disorder characterized by elevated thyroid-stimulating hormone (TSH) levels and normal free thyroxine (FT4) levels. The overdiagnosis and overtreatment of SCH in elderly patients have become concerns as TSH levels naturally increase with age. Studies have shown that many elderly patients with SCH can recover without treatment, and the administration of levothyroxine (L-T4) does not improve their prognosis. Therefore, It is necessary to establish age-specific reference ranges for TSH in elderly individuals to aid in clinical decision-making and prevent overdiagnosis. Methods This is a multicenter prospective study that focuses on Chinese elderly patients with SCH who have TSH levels below 10 mU/L. After obtaining the informed consent of the patients, their initial diagnosis information will be registered, and they will be asked to fill out questionnaires such as the Montreal Cognitive Assessment-Basic (MoCA-B), Hamilton Depression Scale (HAMD), Hypothyroidism Symptom Questionnaire (SRQ), frail scale(FRAIL), fatigue scale, and EQ-5D. In addition, thyroid function tests, blood lipid analysis, carotid artery ultrasound, and thyroid ultrasound examinations will be conducted. Patients will also be grouped according to FT4 levels, the changes in FT4 and its relationship with TSH can also be described. For patients over 80 years old, a decrease in FT4 will be used as an endpoint event, while for patients between 60-80 years old, TSH levels greater than or equal to 10mIU/L or a decline in FT4 will be used as the endpoint event. The TSH reference intervals of the general and elderly populations will be used to calculate medical costs associated with multiple follow-ups of patients, and a social-economic analysis will also be conducted. Discussion This study will prospectively observe elderly patients with SCH who are screened using both age-specific and non-age-specific TSH reference ranges for the elderly population. We will compare the results of elderly patients diagnosed with SCH using different reference ranges and analyze their association with FT4 to identify meaningful SCH patients and reduce over diagnosis and over treatment of elderly SCH. Ethics The Medical Science Research Ethics Committee of the First Affiliated Hospital of China Medical University approved this study (ID: AF-SOP-07-1.1-01). The results will be published in an open-access journal. Clinical trial registration https://www.chictr.org.cn/, identifier ChiCTR2300070831.